'Umbrella construct' – an innovative technique for reconstruction of the proximal humerus after curettage in locally aggressive benign bone tumours. (April 2021) - Gulia, Ashish; Puri, Ajay; Gupta, Srinath; Kurisunkal, Vineet
Aim: Reconstructing locally aggressive benign bone tumours of the proximal humerus after intralesional curettage is a challenge. We present a novel reconstruction technique ' Umbrella construct ' where a femoral head and a strut allograft are combined to reconstruct the cavity. Complications, graft incorporation time, functional (Musculoskeletal Tumor Society score [MSTS]) and oncological outcomes were evaluated. Methods: Between January 2006 and June 2017, 11 cases (10 giant cell tumours, 1 chondroblastoma) underwent curettage followed by reconstruction with Umbrella construct. There were six females and five males with a mean age of 23 years (range 14–36 years). The maximum longitudinal extent of disease was 9 cm (range 5–9 cm). Results: The median follow-up was 54 months (range 34–122 months). The mean allograft incorporation time was 7 months (5–8 months). One patient had a graft fracture which was managed conservatively. Two cases developed local recurrence and the construct was revised to a prosthesis in both. The mean MSTS score for the nine cases with retained graft was 27 (23–29). Conclusions: Umbrella construct is an effective reconstruction modality which helps to maintain joint congruity and limb length. It has acceptable oncological outcomes with good function.